Phase I Trial of Lithium and Tretinoin for Treatment of Relapsed and Refractory Non-promyelocytic Acute Myeloid Leukemia - Ueda, Masumi; Stefan, Tammy; Stetson, Lindsay; Ignatz-Hoover, James J.; Tomlinson, Benjamin; Creger, Richard J.; Cooper, Brenda; Lazarus, Hillard M.; de Lima, Marcos; Wald, David N.; Caimi, Paolo F. (Frontiers in Oncology, 2020)
Glycogen synthase kinase-3 (GSK3) inhibitors induce differentiation and growth inhibition of acute myeloid leukemia (AML) cells. Our pre-clinical studies showed GSK3 inhibition leads to sensitization of AML cells to tretinoin-mediated differentiation. We conducted a phase I trial of lithium, a GSK3 inhibitor, plus tretinoin for relapsed, refractory non-promyelocytic AML. Nine patients with median (range) age 65 (42-82) years were enrolled. All subjects had relapsed leukemia after prior therapy, with a median (range) of 3 (1-3) prior therapies. Oral lithium carbonate 300mg was given 2-3 times daily and adjusted to meet target serum concentration (0.6 to 1.0 mmol/L); tretinoin 22.5 or 45 mg/m2/day (two equally divided doses) was administered orally on days 1-7 and 15-21 of a 28-day cycle. Four patients attained disease stability with no increase in circulating blasts for ≥4 weeks. Median (range) survival was 106 days (60 – 502). Target serum lithium concentration was achieved in all patients and correlated with GSK3 inhibition in leukemic cells. Immunophenotypic changes associated with myeloid differentiation were observed in 5 patients. The combination treatment led to a reduction in the CD34+ CD38- AML stem cell population both in vivo and in vitro. The combination of lithium and tretinoin is well-tolerated, induces differentiation of leukemic cells, and may target AML stem cells, but has limited clinical activity in the absence of other antileukemic agents. The results of this clinical trial suggest GSK3 inhibition can result in AML cell differentiation and may be a novel therapeutic strategy in this disease, particularly in combination with other antileukemic agents. Lithium is a weak GSK3 inhibitor and future strategies in AML treatment will probably require more potent agents targeting this pathway or combinations with other antileukemic agents.